2020
DOI: 10.3174/ajnr.a6554
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Inhomogeneous Magnetization Transfer Imaging Technique to Spinal Cord Damage in Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE: The inhomogeneous magnetization transfer technique has demonstrated high specificity for myelin, and has shown sensitivity to multiple sclerosis-related impairment in brain tissue. Our aim was to investigate its sensitivity to spinal cord impairment in MS relative to more established MR imaging techniques (volumetry, magnetization transfer, DTI). MATERIALS AND METHODS: Anatomic images covering the cervical spinal cord from the C1 to C6 levels and DTI, magnetization transfer/inhomogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“… Zhang et al (2019) reviewed preclinical and validation studies of ihMT and showed good intra- and inter-scanner reproducibility in vivo in human cerebral WM tract; further development and validation are underway ( Cohen-Adad, 2018 ). Lastly, Rasoanandrianina et al (2020) showed that ihMTR was significantly different in the SC of pwMS compared to controls, and that ihMTR showed higher sensitivity to those changes than DTI or MTR metrics. This first study applying ihMTR to the MS SC is promising, and future studies should test the reproducibility of these findings.…”
Section: Advanced Imaging Methodsmentioning
confidence: 92%
“… Zhang et al (2019) reviewed preclinical and validation studies of ihMT and showed good intra- and inter-scanner reproducibility in vivo in human cerebral WM tract; further development and validation are underway ( Cohen-Adad, 2018 ). Lastly, Rasoanandrianina et al (2020) showed that ihMTR was significantly different in the SC of pwMS compared to controls, and that ihMTR showed higher sensitivity to those changes than DTI or MTR metrics. This first study applying ihMTR to the MS SC is promising, and future studies should test the reproducibility of these findings.…”
Section: Advanced Imaging Methodsmentioning
confidence: 92%
“…Several variants of the ihMT technique have been proposed in the past, including single slice 2D ihMT-HASTE (Half-Fourier Acquisition Single-shot Turbo spin Echo) for brain ( Girard et al, 2015 ) and SC ( Girard et al, 2017 , Taso et al, 2016 , Rasoanandrianina et al, 2020 ); 3D ihMT-GRE for brain ( Mchinda et al, 2018 ) and multi-slice ihMT SE- EPI for SC ( Rasoanandrianina et al, 2017 , Rangwala et al, 2013 ). In this study, a 3D ihMT-RAGE sequence initially proposed for brain ( Varma et al, 2020 ), and recently adapted to cervical spinal cord imaging ( Troalen et al, 2018 , Forodighasemabadi et al, 2020:p.1175.…”
Section: Methodsmentioning
confidence: 99%
“…The ihMT method, on the other hand, is more specific to myelin in central nervous system (CNS) tissues ( Varma et al, 2015 , Girard et al, 2015 , Varma et al, 2015 , Duhamel et al, 2019 ). It has been used in several clinical and preclinical studies on brain ( Varma et al, 2015 , Varma et al, 2015 , Prevost et al, 2017 , Mchinda et al, 2018 , Van Obberghen et al, 2018 , Munsch et al, October 2020 , Geeraert et al, May 2017 , Ercan et al, 2018 ) and recently adapted to SC imaging to study demyelinating pathologies such as MS and normal aging ( Girard et al, 2017 , Taso et al, 2016 , Rasoanandrianina et al, 2020 , Rasoanandrianina et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Though there is significant interlesional heterogeneity between patients, attempts have been made to develop a ‘personalized lesion profile’ that could potentially be used as a biomarker of treatment efficacy [25]. The future development of neuro-protective or pro-reparative therapies will heighten the imperative to include such biomarkers in routine MRI monitoring of patients with MS. More hyperintensities-specific imaging techniques such as tract-specific diffusion imaging [26], myelin water imaging [27], inhomogenous magnetization transfer imaging [28] and T1/T2 relaxometry [29] may also play a role, but are beyond the scope of this review.…”
Section: Monitoring the Efficacy Of Disease-modifying Therapiesmentioning
confidence: 99%